Upaya Peningkatan Hasil Belajar Fisika Materi Gerak Lurus Melalui Penerapan Mind Map - Rahimah Rahimah (Dinasti Research, 2022)
The results of observations during physics learning took place in Class VIII-2 students found problems in the teaching and learning process, namely; (1) The teaching and learning process uses conventional methods that it causes students to look bored, bored and passive, (2) The achievement in learning physics is still low. The purpose of this classroom action research was to improve physics learning outcomes. One effort to overcome the problems mentioned above is by applying the Mind Map learning method or concept maps. The research subjects were all students of class VIII-2 MTsN 10 Bireuen, totaling 32 students. Data analysis used descriptive analysis techniques. The results showed that the application of the Mind Map (concept map) in learning physics material in straight motion for class VIII-2 students could improve learning outcomes, where in cycle 1, the number of students who completed as many as 20 students, cycle II students who completed 24 students and those who did not complete 8 students and cycle III students who completed 28 students and who did not complete 4 students.